The Effect of Golden Sea Cucumber (Stichopus hermanii) Extracts to Serum LDL Cholesterol level as a Result of Insulin Resistence - Herin Setianingsih; Fatima Sari Suryono Putri; Wahyu Prasasti Mutia Desi; Erlina Yatnasari (Indonesian Journal of Medical Sciences and Public Health, 2020)
ABSTRACT Diabetes mellitus is a metabolic disease characterized by conditions of hyperglycemia as a result of abnormalities in the secretion of the insulin hormone, the work of the insulin hormone, or both. Metabolic disorders caused by diabetes cause lipolysis to increase, thereby increasing the level of VLDL, which will be converted to LDL. LDL disorders are the effects of insulin resistance. Streptozotocin (STZ) can increase serum LDL cholesterol serum levels due to the mechanism of ROS formation. Golden sea cucumber act as anti-hyperlipidemic because they contain EPA-DHA, saponins, and flavonoids. The purpose of these studies to determine the effect of Golden sea cucumber act as anti-hyperlipidemic. Experimental laboratory research is done using the post-test only control group design method. Using simple random sampling with 25 white male Wistar rats divided into five groups, all rats were given standard feeding. Group 1 without STZ induced, group 2-5 were induced STZ first, and then group 3-5 were given golden sea cucumber extract for 21 days with dose 4,25 mg/kg BW, 8,5 mg/kg BW, 12,75 mg/kg BW, per day respectively. At the end of the study, the LDL serum level was measured. The result of One – Way Anova test showed LDL cholesterol serum levels of group rats with STZ induction and given 12,75 mg/kg BW golden sea cucumber extracts (x=7,4 mg/dl) significantly decreased (p=0,005) compared to LDL cholesterol levels of group rats which were only induced by STZ without given golden sea cucumber extracts (x=12,6 mg/dl). This research showed that the administration 12,75mg/kg BW of golden sea cucumber extracts for 21 days reduced serum LDL cholesterol levels because golden sea cucumber contains compounds that work as antioxidants.